2012
DOI: 10.1097/rlu.0b013e318262af7f
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET/CT as a Prognostic Test After 90Y Radioembolization in Patients With Metastatic Hepatic Disease

Abstract: The purpose of this study was to determine FDG PET/CT utility in predicting patient outcome undergoing Y RE for metastatic liver tumors.Thirty-one patients with metastatic tumors to the liver underwent Y RE between March 15, 2007, and May 5, 2011, at our institution. FDG PET/CT imaging was performed on each patient within 3 months before and after undergoing Y RE. Pretreatment and posttreatment FDG PET/CT were evaluated for SUV, number of liver lesions, and presence of disease outside the liver. The Kaplan-Mei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Recently, the degree of tumor uptake of 18 FDG on PET as assessed by the SUV was shown to be an independent prognostic factor in liver metastases [ 26 , 27 ], but some studies have not found a significant association between SUV and prognosis [ 28 30 ]. Apparently, there have been controversial results.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the degree of tumor uptake of 18 FDG on PET as assessed by the SUV was shown to be an independent prognostic factor in liver metastases [ 26 , 27 ], but some studies have not found a significant association between SUV and prognosis [ 28 30 ]. Apparently, there have been controversial results.…”
Section: Discussionmentioning
confidence: 99%
“…7 Computed tomography assessments use size-based revised Response Evaluation Criteria in Solid Tumors (RECIST 1.1) 8 or tumor necrosis-based Choi criteria. 9 Recent reports have shown that FDG PET/CT was useful in predicting the overall survival after Y90-RE in patients with FDG-avid liver metastases 10,11 or primary liver cancers, 12 especially cholangiocarcinomas. 13 The objective of this study is to create a model that predicts patient treatment response from the pretherapy FDG PET/CT scan alone.…”
Section: Introductionmentioning
confidence: 99%
“…The formulation of the dose calculation is given in the Equation where BSA is body surface area. The role of PET in the SIRT treatment has been steadily increasing, not just for treatment planning, but also for prognostic evaluation [25][26][27]. Both tumor volume and standard uptake value are used for prognostic evaluation [22,25,26].…”
Section: Y-90 Microparticlesmentioning
confidence: 99%